Study of sealants for SOFC. (14th December 2016) - Nguyen, Xuan-Vien; Chang, Chang-Tsair; Jung, Guo-Bin; Chan, Shih-Hung; Lee, Win-Tai; Chang, Shu-Wei; Kao, I-Cheng
Abstract: The development of suitable sealants for high-temperature solid oxide fuel cells (SOFC) is a major challenge, as such sealants must withstand harsh conditions. They must be inert at the high temperatures used in SOFC operation (i.e., resistant to environments composed of oxidative and reducing gases), as well as thermo-chemically and thermo-mechanically compatible with the materials with which they are in contact. This paper presents a post-experimental analysis of variously sealants—mica paper, flexible mica paper, and thermiculite 866—used in high-temperature SOFC operation. The sealants are exposed to air or hydrogen at 600 °C–1000 °C for 100 h. The goal of this work is to investigate the thermal expansion properties (thickness expansion, coefficients of thermal expansion CTE and porosity), mechanical stability, and leakage during midterm operation. After the sealants fired at 1000 °C, their relative thicknesses increased to around 0.98, 1.01, and 0.568 mm, respectively. The coefficients of thermal expansion CTEs (600–1000 °C) for mica paper and flexible mica paper were calculated to be from 8.0 × 10 −4 K −1 to 10.0 × 10 −4 K −1, the CTEs of thermiculite 866 were around 1.0 × 10 −4 K −1 . The relative porosity of thermiculite 866, as determined through the density method, changed from 15.4% to 28.7% for temperatures from 600 °C to 1000 °C, respectively. Scanning electron microscopy is used to investigate the structure of thermiculite 866. It is tested for leakage using hydrogen from 500 to 3000 cc min −1 at 25 °C and 800 °C. The leakage rates at 3000 cc min −1 are 4.06% and 8.4% at 25 °C and 800 °C, respectively, showing that thermiculite 866 is a suitable sealant for SOFC applications. Highlights: Three sealants (mica paper, flexible mica paper, and thermiculite 886) were investigated. The thermal-expansion mechanical stability, microstructure and leakage were utilized to evaluate these sealants. Thermiculite 886 is a better candidate as sealant.